Decoy receptor 3 analogous supplement protects steatotic rat liver from ischemia–reperfusion injury. Issue 7 (July 2017) - Li, Tzu‐Hao; Liu, Chih‐Wei; Lee, Pei‐Chang; Huang, Chia‐Chang; Lee, Kuei‐Chuan; Hsieh, Yun‐Cheng; Yang, Ying‐Ying; Hsieh, Shie‐Liang; Lin, Han‐Chieh; Tsai, Chang‐Youh
Abstract : Background : For steatotic livers, pharmacological approaches to minimize the hepatic neutrophil and macrophage infiltration, and cytokine and chemokine release in ischemia–reperfusion (IR) injury are still limited. Tumor necrosis factor (TNF)‐α superfamily‐stimulated pathogenic cascades and M1 macrophage/Kupffer cells (KC) polarization from Th1 cytokines are important in the pathogenesis of IR liver injury with hepatic steatosis (HS). Conversely, anti‐inflammatory M2 macrophages produce Th2 cytokine (interleukin‐4), which reciprocally enhances M2 polarization. Toll‐like receptor 4‐activated KCs can release proinflammatory mediators, skew M1 polarization and escalate liver IR injury. Decoy receptor 3 (DcR3 ) could be potential agents simultaneously blocking the IR liver injury‐related pathogenic changes and extend the survival of steatotic graft. Methods : Rats were fed with methionine and choline‐deficient high‐fat diet (MCD HFD) for 6 weeks to induce HS. Preliminary experiments with HS group and IR group were conducted, and either immunoglobulin G Fc protein or DcR3 analogue was treated for 14 days in all groups to evaluate the severity. In the Zucker rat‐focused experiments, various serum and hepatic substances, M1 polarization, and hepatic microcirculation were assessed. Results : We found that serum/hepatic DcR3 levels were lower in nonalcoholic fatty liver disease patients with HS. DcR3 a protected Zucker rats with HS from IR liver injury. The beneficial effects of DcR3 a supplement were mediated by inhibiting hepatic M1 polarization of KCs, decreasing serum/hepatic TNFα, nitric oxide, nitrotyrosine, soluble TNF‐like cytokine 1A, Fas ligand, and interferon‐γ levels, neutrophil infiltration, and improving hepatic microcirculatory failure among rats with IR‐injured steatotic livers. Additionally, downregulated hepatic TNF‐like cytokine 1A/Fas‐ligand and toll‐like receptor 4/nuclear factor‐κB signals were found to mediate the DcR3 a‐related protective effects of steatotic livers from IR injury. Conclusion : Using multimodal in vivo and in vitro approaches, we found that DcR3 a analogue was a potential agent to protect steatotic liver against IR injury by simultaneous blockade of the multiple IR injury‐related pathogenic changes.